2019
DOI: 10.5125/jkaoms.2019.45.1.29
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of implant stability measured by resonance frequency analysis in different bone types

Abstract: Objectives Bone density seems to be an important factor affecting implant stability. The relationship between bone density and primary and secondary stability remains under debate. The aim of this study was to compare primary and secondary stability measured by resonance frequency analysis (RFA) between different bone types and to compare implant stability at different time points during 3 months of follow-up. Materials and Methods Our study included 65 implants (BioHor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
1
16
0
1
Order By: Relevance
“…Implant failure can be divided into early and late failures based on the time of failure. Early failure is failure to obtain osseointegration within several weeks or months after implant placement, mainly due to poor bone quality, necrosis of bone due to micro-trauma during surgery, bacterial infections around implants, lack of initial stability, immediate or early loading, smoking, or short-length implants [17, 18]. Delayed failure is destroyed osseointegration after functional loading and is thought to have a main cause of infection such as peri-implantitis or excessive overloading [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Implant failure can be divided into early and late failures based on the time of failure. Early failure is failure to obtain osseointegration within several weeks or months after implant placement, mainly due to poor bone quality, necrosis of bone due to micro-trauma during surgery, bacterial infections around implants, lack of initial stability, immediate or early loading, smoking, or short-length implants [17, 18]. Delayed failure is destroyed osseointegration after functional loading and is thought to have a main cause of infection such as peri-implantitis or excessive overloading [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…6 Other variables that may affect PS encompass implant dimensions (length and diameter), surface characteristics (moderately rough or smooth), and number of threads on the implant surface. 3,[7][8][9][10][11] With regard to implant diameter, studies [12][13][14][15] have shown that narrow-(<3.3 mm) and standard-(4.1 mm) diameter dental implants can remain functionally stable in smokers and medically compromised patient in a manner similar to systemically healthy nonsmokers. However, achievement of PS is often challenging when implants are placed in type-IV bone (soft bone), which usually comprises the posterior maxillae.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tapered dental implants demonstrate a higher mechanical stability compared with cylindrical dental implants 6 . Other variables that may affect PS encompass implant dimensions (length and diameter), surface characteristics (moderately rough or smooth), and number of threads on the implant surface 3,7‐11 . With regard to implant diameter, studies 12‐15 have shown that narrow‐ (<3.3 mm) and standard‐ (4.1 mm) diameter dental implants can remain functionally stable in smokers and medically compromised patient in a manner similar to systemically healthy nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study by Sargolzaie et al, [23], there was no statistically significant relationship between bone density on implant stability.…”
Section: Discussionmentioning
confidence: 90%